2016
DOI: 10.1055/s-0036-1584515
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Preeclampsia on the Brain of the Offspring

Abstract: Preeclampsia (PE) is a significant gestational disorder that causes complications in 3-5% of all human pregnancies. Apart from the immediate risks and complications for mother and fetus, both additionally carry elevated lifelong risks for specific complications. Offspring of PE pregnancies (PE-F1) have higher risks for hypertension, stroke and cognitive impairment compared with well-matched offspring (F1) from uncomplicated pregnancies. Prior to the clinical onset of PE, placental angiokines secreted into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 60 publications
0
19
0
2
Order By: Relevance
“…Interestingly, they also found that children born to preeclamptic pregnancies exhibited reduced cerebral vessel radio in the occipital and parietal lobes, suggesting an intriguing hypothesis that vascular anatomic alterations in the population of offspring of preeclamptic pregnancies might be the underling mechanism for alteration in the brain function of those children. This fact may also contribute to increased stroke risk to this young population in later life [127,128]. Other studies have described an increased risk for metabolic and endocrine disease [118,119], depression [130], cerebral palsy [131], poor cognitive outcome [132], or intellectual disabilities [133] in children born from preeclamptic pregnancies compared to non-exposed children.…”
Section: Cardiovascular Adverse Outcomes In the Offspring Born To Prementioning
confidence: 97%
“…Interestingly, they also found that children born to preeclamptic pregnancies exhibited reduced cerebral vessel radio in the occipital and parietal lobes, suggesting an intriguing hypothesis that vascular anatomic alterations in the population of offspring of preeclamptic pregnancies might be the underling mechanism for alteration in the brain function of those children. This fact may also contribute to increased stroke risk to this young population in later life [127,128]. Other studies have described an increased risk for metabolic and endocrine disease [118,119], depression [130], cerebral palsy [131], poor cognitive outcome [132], or intellectual disabilities [133] in children born from preeclamptic pregnancies compared to non-exposed children.…”
Section: Cardiovascular Adverse Outcomes In the Offspring Born To Prementioning
confidence: 97%
“…The preliminary data in the children of pre-eclamptic women suggest subtle differences in brain vascular development, which is thought to be related to intrauterine events. 9 Therefore, while PlGF may not be essential to reproduction it is still likely to be an important influence on pregnancy and vascular development.…”
Section: Plgf In Reproductionmentioning
confidence: 99%
“…Longer term, preeclampsia (especially early-onset preeclampsia and recurring preeclampsia) is also associated with an increased risk of cardiovascular events, including fatal ones [5][6][7][8][9]. Beyond this, preeclampsia also increases the cardiovascular risk profile in the offspring [10], while hypertension, stroke and cognitive impairment are more frequent [11][12][13]. However, this issue is complex since lifestyle and genes overlap here.…”
Section: Introductionmentioning
confidence: 99%